2002
DOI: 10.1089/089771502320914697
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nitric Oxide and Expression of Nitric Oxide Synthase in Spinal Cord after Acute Traumatic Injury in Rats

Abstract: The aim of this study was to observe the time course of NO production and NOS expression in the spinal cord following acute traumatic injury. Rat spinal cord was injured by extradural static weight-compression, which resulted in an incomplete transverse spinal cord lesion with paralysis of the lower extremities. Using this model, measurement of NO by microdialysis and Griess reaction and histological and immunohistochemical examinations using polyclonal antibodies to nNOS and iNOS were performed from immediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 49 publications
4
32
0
Order By: Relevance
“…Xu and co-workers reported a progressive increase in iNOS expression in the injured spinal cord with maximal expression on day 7, and that the high levels of iNOS expression persist for 2 weeks after SCI [33]. Nakahara reported that NO increases with biphasic changes, such as 1-12 and 24 h to 3 days after injury [28]. These animal studies support the finding that NO metabolites in the CSF increase from 1 day to 2 weeks after SCI, even in human.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and co-workers reported a progressive increase in iNOS expression in the injured spinal cord with maximal expression on day 7, and that the high levels of iNOS expression persist for 2 weeks after SCI [33]. Nakahara reported that NO increases with biphasic changes, such as 1-12 and 24 h to 3 days after injury [28]. These animal studies support the finding that NO metabolites in the CSF increase from 1 day to 2 weeks after SCI, even in human.…”
Section: Discussionmentioning
confidence: 99%
“…In animal experiments of SCI, inducible NO synthase (iNOS) is expressed in the spinal cord immediately after SCI, reaches a maximal value at 12 h, and is maintained at this level of expression for 1 week [13,28,33]. Excessive NO production derived from iNOS has cytotoxic effects [5] and induces neuronal apoptosis, causing neural degeneration and neurodysfunction [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…54 Immediately following contusion SCI, concentrations of NO markedly increase and then gradually decrease between 1 and 12 days after injury. 55 ONOO À itself causes significant neuronal loss and locomotor dysfunction when generated in the rat spinal cord in vivo. 56 The endogenous free radical scavenger, superoxide dismutase (SOD) can moderate this reaction.…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Following spinal cord injury, NO levels exhibit a biphasic increase (Nakahara et al, 2002), with an immediate response within 30 min post-injury, and a second, delayed wave of increase, presumably due to inducible nitric oxide synthase (iNOS) activation and the post-traumatic inflammatory response (Conti et al, 2007). Although sildenafil treatment decreases microglial activation/macrophage infiltration in a murine model of multiple sclerosis (Pifarre et al, 2011), sildenafil treatment had no effect on microglial/macrophage staining following contusive SCI.…”
Section: Myers Et Almentioning
confidence: 99%